Evaluation of the role of CRFergic neurotransmission in anxiety and BNST neuronal activity in male and female mice exposed to psychosocial stress - Forero-Castillo, Felipe [UNESP]; Gonzalez-Escobar, Daniel Enrique [UNESP]; Avalo-Zuluaga, Julian Humberto [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Canto-de-Souza, Lucas [UNESP]; Crestani, Carlos C [UNESP]; Rico, Javier Leonardo; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier, 2025)
Anxiety disorders are increasingly prevalent, and the exposure to psychosocial stress is an important influencing factor; however, the underlying neurobiological mechanisms in female populations remain largely unexplored in animal models. This study investigated the role of the corticotropin-releasing factor type 1 receptor (CRF1R) in the bed nucleus of the stria terminalis (BNST) in anxiety-like behaviors induced by vicarious social defeat stress in female and male mice. Swiss-Webster mice underwent 10 sessions of witnessing social defeat stress (WSDS) or witnessing non-aggressive interactions (WNAI). Subsequently, their behaviors were evaluated in the social interaction test (SIT). Twenty-four hours later, each mouse received treatment with the CRF1R antagonist, CP376395, and after 1 h, was exposed to the elevated plus maze (EPM). Immunofluorescence for c-Fos was employed to assess BNST activation. WSDS female mice exhibited anxiety-like behavior, which was effectively reversed by CP3763995. Additionally, these stressed females exhibited greater c-Fos expression in the ventral BNST, a response attenuated by CRF1 receptor blockade. Notably, no significant behavioral or neural activation changes were observed in males under identical conditions. These findings underscore a sex-specific role for CRF1R signaling in the BNST in mediating anxiety-like responses to vicarious stress, highlighting the relevance of this neurobiological mechanism as a potential target for female-focused therapeutic strategies.